Sarcoide equino - Brum, Juliana Sperotto (2010)
Equine sarcoid is a locally aggressive cutaneous neoplasm, described and characterized as a clinical entity by Jackson in 1936. The neoplasm has a worldwide distribution and affects several equine species. It is believed that the cause of sarcoid is this infection by bovine papillomavirus 1 or 2. The combination of certain factors, including cutaneous trauma, genetic predisposition and viral exposure, seem to be involved in the development of the lesions. Sarcoid have no seasonality, no predilection by color or type hair and is considered the most common skin tumor of horses. Due to the lack of data which could characterize this tumor under the sphere of influence of the Laboratório de Patologia Veterinária (LPV) of the Universidade Federal de Santa Maria (UFSM), this dissertation determines the epidemiological aspects and the anatomic distribution of the different clinical forms of equine sarcoid in the state of Rio Grande do Sul. The files of histopathological exams carried out by the Laboratório de Patologia Veterinária of the Universidade Federal de Santa Maria (LPV-UFSM), between January 2000 and March 2010, were reviewed in search of cases of equine sarcoid. Forty cases were selected to determine epidemiological aspects and the anatomical distribution of the various clinical forms of these neoplasms in horses from Rio Grande do Sul. Out of the cases in which the ages were registered in the histopathological reports, 73,0% (27/37) were 1-5 years-old horses. Multiple sarcoids were observed in most of the affected horses (29/40 [72,5%]). The fibroblastic was the most observed clinical form and it occurred in 42,2% (27/64) of the cases. In more than half of the cases (22/40 [55,0%]), sarcoids had a multifocal distribution. Twenty two (55%) out of the 40 horses evaluated had the tumors in the limbs.